Pendampingan Pembuatan Kompos sebagai Solusi Pengelolaan Sampah - Suparyati Suparyati; Fitrianingsih Fitrianingsih (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2022)
Garbage is basically a material that is wasted or disposed of from a source resulting from human activities or natural processes that have no economic value, it can even have a negative economic value because in handling it, either to dispose of it or to clean it requires a large enough cost. Garbage is a problem in all areas, including in Mulyorejo Village, Tirto District, Pekalongan Regency. Mulyorejo village is one of the villages that is included in the village that is a priority for development in Pekalongan Regency because it is included in the category of village poverty laboratory. According to information from the sanitation section of the Tirto II Health Center, environmental problems in the village are about waste management because the residents do not yet have good waste management. Garbage can actually be used as compost, with a note that before being processed into compost, the waste must be sorted first. The only waste that can be used as compost is garbage/organic type. The purpose of this community service activity is to provide education to the people of Mulyorejo Village about good waste management and how to use waste into compost that has use value for the environment. The method used in this Community Service activity is Lecture by giving directions on composting techniques using a mini composter and practicing composting using a mini composter. The result of this activity is an increase in knowledge, understanding and awareness of the people of Mulyorejo village about the importance of sorting out waste before disposing of waste in its place so that it can be processed into compost.